Challenges in the assessment of nursing students in clinical placements: Exploring perceptions among nurse mentors - Bjørg Christiansen; Gertrud Averlid; Cynthia Baluyot; Karin Blomberg; Anne Eikeland; Ingrid Rachel Strand Finstad; Monica Holm Larsen; Katrin Lindeflaten (Nursing Open, 2021)
Abstract Aim The aim was to explore how nurse mentors experience the assessment of nursing students in clinical placements at hospitals and in municipal health care. Design The study is qualitative with an explorative and descriptive design. Methods Based on an interview guide, we conducted 19 individual qualitative interviews and four focus group interviews with nurse mentors from various levels and fields of nursing education at a Norwegian university. Results Feedback in and on action was an integrated part of the formative assessment. In the summative assessment, where the university lecturer also participates, the nurse mentors perceived their role as passive. A disturbing finding was that divergent views on the student's competence sometimes occurred in these situations, thus challenging the credibility of the student assessment. Perceptions of nursing values and concerns embedded in nursing practice as collective criteria appear to have an impact on the mentors’ assessment of the nursing students.